Coronavirus disease 2019 (COVID-19): Considerations for the competitive athlete - Toresdahl, B. G.; Asif, I. M. (Sports Health: A Multidisciplinary Approach, 2020)
As of March 2020, COVID-19 has become a global pandemic, halting athletic competition worldwide. Current focus is on the prevention of viral spread through social distancing and other common hygiene measures. Sports medicine providers should know the most common symptoms of COVID-19, work within their environments to learn and develop testing protocols as indicated by local resources, and minimize spread among teams. Treatment in the outpatient setting is mainly supportive and includes home isolation, although several treatment drugs are under clinical investigation.